Optimal bidding strategies and modeling of imperfect information among competitive generators. - Fushuan Wen
The emerging electricity market behaves more like an oligopoly than a perfectly competitive market due to special features such as, a limited number of producers, large investment size (barrier to entry), transmission constraints, and transmission losses which discourage purchase from distant suppliers. This makes it practicable for only a few independent power suppliers to service a given geographic region and in this imperfect market each power supplier can increase its own profit through strategic bidding. The profit of each supplier is influenced to varying extents by differences in the degree of imperfection of knowledge of rival suppliers. A new framework to build bidding strategies for power suppliers in an electricity market is presented in this paper. It is assumed that each supplier bids a linear supply function, and that the system is dispatched to minimize customer payments. Each supplier chooses the coefficients in the linear supply function to maximize benefits, subject to expectations about how rival suppliers will bid. A stochastic optimization formulation is developed and two methods proposed for describing and solving this problem. A numerical example serves to illustrate the essential features of the approach and the results are used to investigate the potential market power
Keywords: Monte Carlo simulation; Competitive generators; Competitive market; Customer payments minimisation; Electricity market; Imperfect information modeling; Independent power suppliers; Large investment size; Linear supply function; Optimal bidding strategies; Power suppliers; Stochastic optimization; Strategic bidding; Transmission constraints; Transmission losses